Debt sustainability analysis for euro area sovereigns: A methodological framework - Othman Bouabdallah; Cristina Checherita-Westphal; Thomas Warmedinger; Roberta De Stefani; Francesco Drudi; Ralph Setzer; Andreas Westphal (European Central Bank (ECB), 2017)
The euro area sovereign debt crisis has highlighted the importance of reducing public debt levels and building up sufficient fiscal buffers during normal and good times. It has also reaffirmed the need for a thorough debt sustainability analysis (DSA) to act as a warning system for national policies. This paper introduces a comprehensive DSA framework for euro area sovereigns that could be used for analysis of fiscal risks and vulnerabilities. Specifically, this framework consists of three main building blocks: (i) a deterministic DSA, which embeds debt simulations under a benchmark and various narrative shock scenarios; (ii) a stochastic DSA, providing for a probabilistic approach to debt sustainability; and (iii) other relevant indicators capturing liquidity and solvency risks. The information embedded in the three main DSA blocks can be summarised in a heat map, which can provide guidance on the overall assessment of risks to debt sustainability. This method reflects the need to have a broad-based assessment, cross-checking information and perspectives from various sources with a view to deriving a robust debt sustainability assessment.
Keywords: E62; H62; H63; H68; 330; sovereign debt sustainability analysis; fiscal policy; public debt; euro area; fiscal risks